ANALYSIS ON THE EFFECT OF MARKETING MIX ON CUSTOMER SATISFACTION AND LOYALTY IN THE HOSPITALITY INDUSTRY OF ETHIOPIA: USING STRUCTURAL EQUATION MODEL. - Gebremichael, Abraha Haftom; Dhillon (PhD), Parminder Singh (The journal of contemporary issues in business and government, 2022)
In contemporary service marketing strategy, more attention has been given to the very concept of the 7ps marketing mix as a package and are believed to be crucial tools to bring about Customer satisfaction and loyalty thereby maximize company’s performance. Having this into account, the study mainly aims at examining the impact of marketing mix and customer satisfaction on customer loyalty of hotel industry in Ethiopia. The study used 387 participants who were staying in some selected 3star hotels during the time of data collection andrandomly approached using self-administered questionnaire. Structural equation model, specifically exploratory and confirmatory factor analyses were used to analyze the data. To this end, findings of the study showed that marketing mix and customer satisfaction has positive significant effect on customer loyalty. The study gives a clue to hospitality marketers that better engagement on marketing mix and customer satisfaction are best ways to ensure sustainable customer loyalty.